PERGULATAN OTORITAS DAN OTORITARIANISME DALAM PENAFSIRAN: (Pembacaan Hermenuetis Khaled Abou El Fadl) - Moh. Muhtador (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
This article specifically studied about Khaled Abou el Fadl’s thought about the authority and authoritarianism in the interpretation. The Qur’an, divine Kalam, has the ultimate authority in human life, where it’s part of God’s manifestation in realizing the intent and purpose. The effort to understand the Qur’an has been done since the verse was revealed and even developed in accordance with the times and has produced many exegetical products, such as Sufi interpretation, fiqh, philosophy, etc. The Divine Message neatly arranged in the Qur’an has been shaped a text. The text as a sign represents the Divine purpose in conveying its meaning. Therefore, the reader must be wise and careful in understanding the text of the Qur’an. If the reader is careless in understanding al Qur’an though only slightly, they will be authoritarian people.